Association of acceleration with spatiotemporal variables in maximal sprinting - Nagahara, R.; Naito, H.; Morin, J.-B.; Zushi, K. (International Journal of Sports Medicine, 2014)
This study clarified the association between acceleration and the rates of changes in spatiotemporal variables on a step-to-step basis during the entire acceleration phase of maximal sprinting. 21 male sprinters performed a 60-m sprint, during which step-to-step acceleration and rates of changes in step length (RSL) and step frequency (RSF) were calculated. The coefficients of correlation between acceleration and other variables were tested at each step. There were positive correlations between acceleration and the RSF up to the second step. Acceleration was positively correlated with the RSL from the 5th to the 19th step. At the third and from the 16th to the 22nd step and from the 20th to the 21st step, there was no significant correlation, but weak relationships were found between acceleration and the RSF and RSL. The results suggest that the acceleration phase can be divided into 3 sections, and for sprinting to be effective, it is important to accelerate by increasing the step frequency to the third step, increasing the step length from the 5th to the 15th step, and increasing the step length or frequency (no systematic relative importance of step length or frequency) from the 16th step in the entire acceleration phase.